PREPARATION OF CHITOSAN-CELLULOSE COMPOSITE BEADS USING CELLULOSE ISOLATED FROM SUGARCANE BAGASSE - Rahmi Rahmi; Alfahmizar Alfahmizar; Lelifajri Lelifajri (Universitas Syiah Kuala, 2019)
Chitosan-cellulose composite beads had been prepared using cellulose isolated from sugarcane bagasse. Sugarcane bagasse was hydrolyzed with H2SO4 with various concentrations (30, 40, and 50%). Cellulose obtained was characterized using Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). FTIR analysis results inform the existence of typical functional groups of cellulose in the sample. XRD patterns show H2SO4 concentration on the hydrolysis process influence the crystallinity of cellulose. Cellulose was used as a filler in the preparation of chitosan-cellulose composite beads. The results show that cellulose decrease the crystallinity of chitosan.